STATISTICAL ANALYSIS OF THE DEVELOPMENT OF THE WORLD ELECTRONIC TRADE MARKET - SAHER, LIUDMYLA; SYHYDA, LIUBOV; RESHETNIAK, YAROSLAV; SHEVCHENKO, KATERYNA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
Nowadays e-commerce develops rapidly. Volumes of online sales grow globally. E-commerce forms a separate sector of the economy. Moreover, e-commerce is at the peak of its popularity. The article aims to analyze the development of the e-commerce market worldwide and to identify the further prospects of its development. The article analyzes the world e-commerce market. The volumes of products online-sales in the dynamics since 2014 are determined. The volumes of sales in the e-commerce market by regions of the world are studied. The largest one is the Asia-Pacific region. It accounts for 62.6% of all e-commerce sales. It is followed by the North American region (19.1% of all global e-commerce sales) and the Western Europe region (12.7% of all global e-commerce sales). It is established that global sales figures are significantly influenced by China and the United States of America. These countries rank the first and the second places responsively in the world in terms of products' sales in the e-commerce market. Similar indicators for the European e-commerce market are analyzed. The dynamics of the growth of online shoppers in different European countries are determined. The payment methods that online shoppers use most often are highlighted. The most popular methods in many countries are debit and credit card payments. Nevertheless, German online shoppers prefer ELV payments, and online shoppers from the Netherlands choose IDEAL. The most popular categories of online products are small appliances, books, clothing and shoes, computers and accessories, tickets. People like to buy online products at lower prices and universe products. The reason is that the target audience of universe products is not limited by age, body composition, psychological complexes, and other factors that can potentially reduce interest in the products. The results of this study determine the expediency and perspective directions of world e-commerce development.
Keywords: world trade; e-commerce; retailing; payment methods; online purchase